DEVELOPMENT OF OFFICIAL INDONESIA STANDARD TIME : TEMPERATURE CONTROL SYSTEM FOR CAESIUM ATOMIC CLOCK - Windi Kurnia Perangin-Angin; Mohamad Boynawan; Ratnaningsih Ratnaningsih (Instrumentasi, 2021)
Every country should have an official time standard which called local coordinated universal time, UTC(k). Badan Standardisasi Nasional (BSN) has developed an official standard time, namely UTC(IDN) which is used as Indonesia Standard Time. The UTC(IDN) contributes to calculation of coordinated universal time (UTC). In order to generate the UTC(IDN), the output of 1 pulse per second signal of caesium atomic clock is utilized as the actual signals of this standard. A distribution amplifier is used to distribute the signal. Combination of time transfer system (TTS-3) and GPS are employed for comparison of UTC and UTC(IDN). TTS-3 automatically calculated the difference and it is steered by using certain algorithm. Time synchronization to the standard can be conducted through network time protocol (NTP) server, i.e., ntp.bsn.go.id. The time can be automatically synchronized using internet time or certain program at each computer or machine. The results of this work show that the time differences between UTC – UTC(IDN) vary from 43.2 ns to 1729.9 ns. UTC(IDN) has frequency and time stability of 3.6 x 10-14 Hz/Hz per 5 days and 3.1 ns per 5 days, respectively which are in good agreement to the international time reference. A shielding chamber with temperature control system has been built to keep the ambient temperature of caesium atomic clock at (23 ± 1) ᵒC. It can be concluded that BSN has been developing and disseminating the UTC(IDN) as an Indonesia Standard Time that can support the regulation of time synchronization in Indonesia. A new temperature control system is proposed to stabilize the ambient temperature of caesium atomic clock. The temperature control system supports an accurate and stable UTC(IDN).